AETA 2013: Recent Advances in Electrical Engineering and Related Sciences - Zelinka, Ivan; Duy, Vo Hoang; Cha, Jaesang (Lecture Notes in Electrical Engineering, 2014)
Over the past decades, fault diagnosis (FDI) and fault tolerant control strategies (FTC) have been proposed based on different techniques for linear and nonlinear systems. Indeed a considerable attention is deployed in order to cope with diverse damages resulting in faults occurrence.